2023
DOI: 10.7557/cage.6917
|View full text |Cite
|
Sign up to set email alerts
|

CAGE20-8 Cruise Report: Natural gas seepage and past sea ice variability on the NE Greenland margin

Abstract: CAGE20-8 cruise onboard RV “Kronprins Haakon” aimed to survey the natural seepage of methane along the NE Greenland margin. Based on multibeam echosounder surveys, water column mapping for gas flares, and shallow seismic, gravity coring and multicoring were conducted. Due to heavy ice conditions, the vessel did not reach the shelf, however, survey along the continental slope were conducted. From a number of acoustic profiles and sediment cores, we will pursue the investigations of natural seepage related to gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…2. We demonstrated that methane content in highly active methane seepage areas is controlled by current rather than by vertical methane transport, limiting the escape to the atmosphere (Silyakova et al, 2020) 3. We showed how chemical diversity of dissolved organic matter at marine methane seeps is higher than non-seep areas (Sert et al, 2020) 4.…”
Section: Main Achievements 2020mentioning
confidence: 92%
“…2. We demonstrated that methane content in highly active methane seepage areas is controlled by current rather than by vertical methane transport, limiting the escape to the atmosphere (Silyakova et al, 2020) 3. We showed how chemical diversity of dissolved organic matter at marine methane seeps is higher than non-seep areas (Sert et al, 2020) 4.…”
Section: Main Achievements 2020mentioning
confidence: 92%